Tiga menit mematikan: Korps Baret Merah dalam operasi pembajakan pesawat DC-9/Woyla (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
The main issue discussed was how the Red Beret Corps, which is the Indonesian Special Forces, managed to carry out military operations outside Indonesian jurisdiction to free the DC-9 / Woyla aircraft hostage that had been hijacked by a group of people who called themselves Komando Jihad. Moreover, the Red Beret Corps did not have military experience in handling acts of terror. When the hijackers took hostage, the hijackers asked the pilot to fly the plane anywhere which would make it difficult for the Indonesian government to exercise military options. The research method used is the historical method which includes heuristics, source criticism, interpretation and historiography. Based on the research results, apart from having great soldiers, the Red Beret Corps also had reliable leaders. Sintong Panjaitan, who is the leader in the DC-9 / Woyla hijacking operation, is believed to be able to overcome this situation because of his experience in observing anti-terror special forces exercises abroad. This is evident from the planning, training and raid stages, Sintong was able to design the first anti-terror force in the Red Beret Corps and succeeded in releasing aircraft hostages in a short time without a single hostage being injured.
Keywords: Aircraft Hijacking; Red Beret Corps; Military Operations